Best Answer

5x + 6 - 2x = -5 - x

Reduce the x variables on the left side of the equation:

3x + 6 = -5 -x

Move the x variables to the same side of the equation

3x + x + 6 = -5 - x + x

4x + 6 = -5

Move the non-variable numbers to the other side of the equation

4x + 6 - 6 = -5 - 6

4x = -11

Divide by 4, to give you x on its own

4x/4 = -11/4

x = -11/4 = -2.75

Q: What is the answer to 5x plus 6 - 2x equals -5 - x?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8

5x - 4 = 3x + 6 5x - 3x = 6 + 4 2x = 10 x = 5

5X + 6 = 2X + 15 -2X -2X 3X + 6 = 15 -6 -6 3X = 15 ---- ----- 3 3 x = 5 im so smart.

2x + 5 + 3x = 25 5x + 5 = 25 Subtract 5 from both sides: 5x = 20 Divide both sides by 5: x = 4

5x

Related questions

3x + 2 + 2x = 7; 3x + 2x = 5x, so 5x + 2 = 7; 7-2=5, so 5x=5. 5x divided by 5 and 5 divided by 5 equals 1, so x equals 1.

7x = 5+5x 7x-5x = 5 2x = 5 x = 2.5

2x + 5x = 35 7x = 35 x = 35/7 x = 5

x+2x+14=5x+214-2=5x+2x+x10=8x10/8=xx=5/4 ans.

5x - 2x = -5 - 1 ie 3x = -6 so x = -2

x = -5

5

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5

3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8

-3x + (-18) = 2x + 7 +18 +18 -3x = 2x +25 -2x -2x -5x = 25 ----- ----- -5 -5 x=-5 *------- equals a division line

2x + 5x = 357x = 35x = (35 / 7) = 5

x=1 2/3 How?: 2x-4+3 = 5x-6 2x-1 = 5x-6 2x-1+1 = 5x-6+1 2x = 5x-5 2x-5x = 5x-5x-5 -3x = -5 -3x/-3 = -5/-3 x = 5/3 x = 1 2/3